Integrative taxonomy and molecular phylogenetic analysis of bent-winged fireflies (coleoptera: lampyridae: pteroptyx) in Peninsular Malaysia and Sarawak - W. Jusoh, Wan Faridah Akmal (2015)
Species delineation using integrative taxonomy has become popular since about a decade ago. Integrative taxonomy entails the use of multiple tools including DNA barcoding and morphological examination of specimens. Integrative taxonomy has reduced major problems in taxonomy such as the presence of cryptic species and the overabundance of synonymous names. In this study, the application of integrative taxonomy in Malaysian firefly taxonomy was presented. To do so, the diversity of fireflies in mangrove estuaries was explored by combining data of geographic distribution, morphology, DNA sequencing and phylogeny of fireflies. The geographic location was restricted to 11 mangrove sites in Malaysia, from which 756 specimens were studied. Morphological data was found to be compatible with molecular data and all species were monophyletic, i.e. both indicated 12 species including non-bent-winged firefly species. However, inclusion of females and larvae in DNA barcoding analysis increased the species count to 14 species. Using combined molecular datasets of three genes (mitochondrial DNA (mtDNA) cytochrome oxidase I (COI), mtDNA fragment containing the 3’ end of COI gene, the adjacent complete of tRNAleu gene and the 5’ end of the COII gene (COI-COII) and nuclear protein coding gene CAD)), the Bayesian analysis revealed that Pteroptyx was a monophyletic clade but it was clustered into two groups: A. (Pteroptyx asymmetria + P. tener + P. bearni); B (Pteroptyx gelasina, Pteroptyx malaccae and Pteroptyx valida). The intraspecific variations in two bent-winged firefly species, Pteroptyx bearni Olivier and Pteroptyx tener Olivier arising from geographical isolation were confirmed. The analysis also supported the position of P. gelasina in the same clade with P. malaccae but with strong posterior probability to be distinguished as a distinct species. Consequently, a list of species and DNA barcode reference library of Malaysian fireflies were created for the first time. This study therefore supports the perspective that integrative taxonomy will speed up species discovery while maintaining species inventories. The application of such information for firefly and mangrove conservation is highly recommended.